Surgical fasciectomy versus collagenase injection in treating recurrent Dupuytren disease: study protocol of a randomised controlled trial. Issue 2 (25th February 2019) - Nordenskjöld, Jesper; Lauritzson, Anna; Waldén, Markus; Kopylov, Philippe; Atroshi, Isam
Abstract : Introduction: There is no definitive cure for Dupuytren disease (DD), and recurrence of finger contractures after treatment is common. Surgical fasciectomy is considered the standard treatment method for recurrence, although associated with a high incidence of complications. Collagenase injection, a non-surgical treatment option, has been shown to be a safe and effective method; however, most studies regarding collagenase have involved first-time treatment. Collagenase efficacy in patients with recurrent DD beyond the immediate effect has not yet been determined. The aim of our study is to compare surgical fasciectomy and collagenase injection in treating recurrent DD. Methods and analysis: The study is a single-centre randomised controlled trial. Inclusion criteria are recurrence of DD in one or more fingers after previous treatment with fasciectomy or collagenase injection, a passive extension deficit ≥30° in the metacarpophalangeal (MCP) and/or proximal interphalangeal (PIP) joint, and a palpable cord causing the recurrent contracture. A total of 56 patients will be randomised to either surgical fasciectomy or collagenase injection. A hand therapist blinded to patients' group allocation will measure range of motion at baseline, 3 months, 12 months, 24 months and 60 months. The primary outcomes are the total active extension deficit (MCP plus PIP) at 3 months and the proportion of patients with contracture worsening ≥20° in the treated finger joint at 2 years compared with 3 months. The secondary outcomes include changes in total active motion, active and passive extension deficit from baseline up to 5 years, scores on patient-reported outcome measures, adverse events and costs of treatment. Ethics and dissemination: Ethical approval has been obtained from the Regional Ethical Review Board, Lund University, Sweden(2017/623). The trial will be conducted according to the Helsinki Declaration of 1975, revised in 2000. The results of the trial will be disseminated as published articles in peer-reviewed journals. Trial registration: NCT03406338 ; Pre-results.